2019
DOI: 10.13189/ujer.2019.070923
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Headmasters' Leadership and Its Effect on Job Satisfaction of Special Education Integration Program (PPKI) Teachers in Johor, Malaysia

Abstract: Teachers in the special integration education program (PPKI) in Johor do not feel satisfaction in working, especially in the teaching and learning process for pupils with special needs. This problem exists due to various factors, such as the high burden of duties, the special circumstances of students who are unable to manage themselves, the readiness of the teachers themselves and the leadership of the headmasters. From all the factors mentioned, the headmasters' leadership factor has a very significant influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 2 publications
3
9
0
1
Order By: Relevance
“…According to Ali (2020), attitude in carrying out tasks, indicates a person's contribution to the organization in which they serve. This finding is also in line with the statement by Norazmi et al, (2019) which describes that work attitude demands a person in focusing on the best service to their organization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to Ali (2020), attitude in carrying out tasks, indicates a person's contribution to the organization in which they serve. This finding is also in line with the statement by Norazmi et al, (2019) which describes that work attitude demands a person in focusing on the best service to their organization.…”
Section: Discussionsupporting
confidence: 90%
“…Teachers who have good emotional control can help in producing a quality work attitude. Norazmi et al, (2019) also agree with that opinion by stating that, a positive attitude guarantees stable emotions in performing tasks. Fiftyana (2018) also gives a statement that is in line with this finding, which is a work attitude that meets stable emotional needs, enabling a person to perform work well and productively.…”
Section: Discussionsupporting
confidence: 53%
“…Before going to schools to have an observation program, they listed several points to be observed in the observation sheet (Wu et al, 2016). However, they found several additional important points to consider during their observation program (bin Nordin et al, 2019). First, they cover all teaching and learning activities in English classes in Senior High Schools and Vocational High Schools.…”
Section: Resultsmentioning
confidence: 99%
“…Literature has shown that universities play an important role in fostering entrepreneurship (Viviers et al, 2013;Nik Nurharlida et al, 2021). Its teaching practices vary from work-based learning to theoretical models and it cuts across psychology, economics, finance and social studies (Schuh et al, 2015;Norazmi et al, 2019;. This suggests that it is interdisciplinary in nature (Mkwanazi and Mbohwa, 2018).…”
Section: Introductionmentioning
confidence: 99%